Faktor yang Berhubungan dengan Motivasi Perawat Bagian Rawat Inap di Rumah Sakit Khusus Daerah Kota Makassar - Husnayain, Ihdal; Andayanie, Ella; Septiyanti, Septiyanti (Window of Health : Jurnal Kesehatan, 2019)
Motivation is an impulse that comes from within a person that will direct one's actions with the aim of achieving a desired result. Nurses' complaints about the conditions of work and the lack of appreciation for the work results sometimes as a trigger for the low work motivation of many causes that result in low levels of work motivation of nurses. This study aims to determine the factors associated with motivation of nurses, especially in the inpatient section of the Makassar City Special Hospital. This research is a quantitative study with a cross sectional study approach, using the Chi Square test which aims to determine the relationship between the dependent variable and the independent variable. The sample in this study amounted to 64 nurses inpatient using total sampling techniques. There is no relationship between wages, opportunities for advancement, work environment and recognition of achievement on nurse motivation. Statistical test results using chi-square obtained p values, each p = 0.763, p = 1.00, p = 0.615, and p = 0.774. The motivation level of nurses is less than 57.8%, and nurses with sufficient motivation are 42.2%. There is no relationship between wages, opportunities for advancement, work environment, and recognition of achievement and motivation of nurses inpatient. It is expected that hospital leaders should pay attention to nurses' complaints in the hospital so that nurses work motivation in providing nursing services to patients better in the future, and for hospitals to give more appreciation to nurses.